Analisis Penerapan Prinsip Layout, Tipografi, Warna, dan Gambar Pada Sampul Majalah Dinamika - Heri Setiawan; Gamal Kartono (Mahesa Research Center, 2021)
This study aims to analyze and describe how the cover of the student press magazine Dinamika State Islamic University of North Sumatra applies magazine cover design based on the principles of layout, typography, and color selection and images. This study uses a qualitative descriptive method. The subject of this research is the student press magazine Dinamika UIN SU edition 29 to edition 50 with a total of 15 magazine covers using purposive sampling technique. The results of this study explain the number of magazine covers that apply the very good category layout principle as many as 5 covers (33%), 5 good (33%), 3 good enough (20%), and 2 cover (14%) less good. The application of the principles of typography in very good categories was 4 covers (27%), 6 good (40%), 1 (6%) good enough, and 4 covers (27%) not good enough. Color selection for very good categories was 7 covers (47%), good 3 (20%), good enough 4 (27%), and less good as many as 1 cover (6%). In the selection of images, there were 3 covers (20%), 6 (40%), 2 (14%) good enough, and 4 (27%) not good. Overall, the results of this study concluded that the quality of the application of the principles of layout, typography, colors, and images on the cover design of the UIN SU student press magazine Dinamika was categorized as quite good.